2005
DOI: 10.1162/0898929055002436
|View full text |Cite
|
Sign up to set email alerts
|

An ERP Study of Second Language Learning after Childhood: Effects of Proficiency

Abstract: Whether there is an absolute critical period for acquiring language is a matter of continuous debate. One approach to address this issue is to compare the processes of second language (L2) learning after childhood and those of first language (L1) learning during childhood. To study the cortical process of postchildhood L2 learning, we compared event-related brain potentials recorded from two groups of adult Japanese speakers who attained either high or intermediate proficiency in English after childhood (J-Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
187
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(212 citation statements)
references
References 40 publications
20
187
2
3
Order By: Relevance
“…The pattern observed in the deaf participants in the present study is not consistent with ERP evidence from hearing L2 English-speakers who evidenced explicit understanding of agreement in the absence of implicit awareness (Hahne, 2001;Ojima et al, 2005;Weber-Fox & Neville, 1996). This difference might be due to the fact that second language learners tend to undergo explicit training on subject-verb agreement, which allows them to explicitly apply a rule when asked to do so.…”
Section: Discussioncontrasting
confidence: 99%
“…The pattern observed in the deaf participants in the present study is not consistent with ERP evidence from hearing L2 English-speakers who evidenced explicit understanding of agreement in the absence of implicit awareness (Hahne, 2001;Ojima et al, 2005;Weber-Fox & Neville, 1996). This difference might be due to the fact that second language learners tend to undergo explicit training on subject-verb agreement, which allows them to explicitly apply a rule when asked to do so.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Hahne (2001) demonstrated a P600 response to L2 phrase structure violations in proficient Japanese learners of German, but did not observe an early anterior negativity sometimes seen in L1 studies of the same violation. An atypical P600 response to a phrase structure violation was observed by Hahne and Friederici (2001) in late L2 learners, and Ojima, Nakata, and Kakigi (2005) did not observe a P600 to English (L2) subject-verb agreement violations in Japanese (L1) late learners, although an N400 response was observed in higher-proficiency learners. Tokowicz and MacWhinney (2005) observed a P600 response in early English learners of Spanish to Spanish tense and gender violations.…”
Section: Introductionmentioning
confidence: 72%
“…It has been argued that a LAN effect in L2 speakers arises only at the highest level of (native-like) proficiency, whereas P600 effects occur earlier during L2 acquisition (Steinhauer et al, 2009). However, not all available results point in this direction (e.g., Ojima et al, 2005, found only the early effect, but not a P600 in highproficiency speakers processing subject-verb agreement in English). Furthermore, this claim is of course based on the assumption that the used manipulation does cause LAN effects in native speakers, which, as we have just argued, is not always the case.…”
Section: Introductionmentioning
confidence: 92%
“…As many foreign language learners only start to use that foreign language intensively when they are adults, most of them experience that it is hard to reach perfection in that new language: It is estimated that only 5-15% of adult second language (L2) learners reach native-like levels of proficiency (Birdsong, 2004). This holds particularly for domains like pronunciation and syntax, whereas semantic processing is often found to be comparable to that of natives from early on during L2 acquisition (Ojima, Nakata, & Kakigi, 2005;Duyck & Brysbaert, 2004;Stenberg, Johansson, & Rosen, 2004;Hahne & Friederici, 2001).…”
Section: Introductionmentioning
confidence: 99%